Characterizations and growth kinetics of the borided layer formed on pure nickel by molten salt electrolysis - Wang, Bixia; Yuan, Wenlong; Wang, Ziyu; Li, Jianxin; Ma, Hongzhou; Song, Yonghui (Journal of Mining and Metallurgy, Section B: Metallurgy, 2022)
Molten salt electrolysis was applied for the boronizing of nickel with Na2B4O7·10H2O-Na2CO3 as the electrolyte and characterizations and the growth kinetics of borided layer is reported. The experiment was carried out in silicon carbide crucible at 1193 K, 1223 K, and 1243 K for 1 h, 2 h, 3 h, and 4 h. The morphology and phases formed on the surface of pure nickel were analyzed by means of scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), and X-ray diffraction analysis (XRD). The surface hardness and corrosion resistance of the boronized sample were tested by micro hardness tester and electrochemical workstation, respectively. The borided layer was composed of nickel borides and its thickness ranged from 71 to 184 μm. After 1 h of boronizing, the hardness of the silicon rich borides is 966 HK, which is a little lower than that of the nickel borides (992-1008 HK); the surface hardness reached 1755 HK after 4 h electrolysis. Electrochemical impedance spectroscopy analysis showed that the corrosion resistance of boronized sample is better than that of pure nickel. Borided layer growth kinetics was studied by analyzing the relationship between thickness of the borided layer and time by mathematical method. Then the diffusion coefficient constant of boron atom in nickel at 1193 K, 1223 K and 1243 K was calculated accordingly and an equation was obtained to estimate the thickness of the borided layer.